Analysis of friction reduction effect due to ultrasonic vibration exerted in friction stir welding. (October 2018) - Yang, C.L.; Wu, C.S.; Shi, L.
Abstract: A model is developed to characterize the ultrasonic induced friction reduction in ultrasonic vibration enhanced friction stir welding (UVeFSW). Two effects, i.e., acoustic softening and ultrasonic induced friction reduction (UiFR), are both considered in analyzing the heat generation, temperature profile and material flow in UVeFSW. It is found that at the tool/workpiece contact interfaces the friction coefficient shows a butterfly-like distribution if the ultrasonic induced friction reduction (UiFR) is taken into consideration. With UiFR, the predicted heat generation in UVeFSW is more reasonable, the predicted TMAZ (thermo-mechanically affected zone) boundary is in more agreement with the measured one, and the calculated thermal cycles match better with the experimentally measured ones.